2007
DOI: 10.1042/bj20070271
|View full text |Cite
|
Sign up to set email alerts
|

Thrifty Tbc1d1 and Tbc1d4 proteins link signalling and membrane trafficking pathways

Abstract: Establishing a complete pathway which links occupancy of the insulin receptor to GLUT4 translocation has been particularly elusive because of the complexities involved in studying both signalling and membrane trafficking processes. However, Lienhard's group has now discovered two related molecules that could function in this linking role. These proteins, Tbc1d4 (also known as AS160) and now Tbc1d1, as reported in this issue of the Biochemical Journal, have been demonstrated to be Rab GAPs (GTPase-activating pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This pathway involves phosphorylation of TBC1D4 by protein kinase AKT and have led to its alternative designation as AKT substrate of 160 kDa (AS160) (32,33,38,40,44). Experimental suppression of TBC1D4 leads to leaky and insulin-independent release of GLUT4 into the plasma membrane (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway involves phosphorylation of TBC1D4 by protein kinase AKT and have led to its alternative designation as AKT substrate of 160 kDa (AS160) (32,33,38,40,44). Experimental suppression of TBC1D4 leads to leaky and insulin-independent release of GLUT4 into the plasma membrane (45).…”
Section: Discussionmentioning
confidence: 99%
“…WNK1 Leads to Increased Expression of GLUT1 at the Cell Surface-In insulin-sensitive adipocytes and skeletal muscle cells TBC1D4 was shown to control the translocation of the insulin-responsive glucose transporter GLUT4 from intracellular storage vesicles to the plasma membrane (33,38). Most other cell types, however, express the transporter GLUT1 for their constitutive uptake of glucose (39).…”
Section: Wnk1 Exists In a Complex With Tbc1d4-mentioning
confidence: 99%
“…A number of studies in cultured cells, predominantly 3T3-L1 adipocytes and L6 muscle cells, subsequently established the following model for AS160 function in GLUT4 trafficking (23). Under basal conditions, AS160 localizes to GLUT4 vesicles and is active as a Rab GAP.…”
mentioning
confidence: 98%
“…Skeletal muscle glucose uptake is accompanied by increased GLUT4 translocation; both insulin and contraction independently stimulate GLUT4 translocation in vivo [10]. One of the main differences between Tbc1d1 and Tbc1d4 is the occurrence of an AMPK (AMP-activated protein kinase) phosphorylation site between the two PTB domains of Tbc1d1 [9]. The PTB domain seems to be relevant for the implication of Tbc1d1 in energy homeostasis, since a non-conservative mutation (R125W) in the PTB domain of Tbc1d1 has recently repeatedly been shown to be associated with severe familial obesity in humans [11,12].…”
mentioning
confidence: 99%
“…In addition, they showed that insulin led to the phosphorylation of Tbc1d1 on a binding site for Akt that is conserved between Tbc1d1 and Tbc1d4. Moreover, Tbc1d1, like Tbc1d4, mediated GLUT4 translocation through an Akt-mediated decrease of Rab GAP activity, indicating that a high level of Rab GAP activity causes suppression of GLUT4 translocation (and thus glucose uptake), whereas a decrease of Rab GAP activity does the opposite [7,9]. In light of this observation, the identified SJL-specific loss-of-function mutation in Tbc1d1 by Chadt et al [1] would thus be expected to contribute to decreased levels of blood glucose through an increased GLUT4 translocation.…”
mentioning
confidence: 99%